Multilocus Sequence Typing Reveals Clonality of Fluconazole-Nonsusceptible Candida tropicalis: A Study From Wuhan to the Global - Wang, Qianyu; Tang, Dongling; Tang, Kewen; Guo, Jing; Huang, Yun; Li, Congrong (Frontiers in Microbiology, 2020)
Candida tropicalis is a globally distributed human pathogenic yeast, and its increasing resistance to azoles makes clinical treatment difficult. In this study, we investigated the clinical features, azole resistance and genetic relatedness of 87 C. tropicalis isolates from central China and combined with the global database to explore the relationship between genetic information and fluconazole susceptibility. Of the 55 diploid sequence types (DSTs) identified by multilocus sequence typing (MLST), 27 DSTs were new to the C. tropicalis MLST database. Fluconazole-nonsusceptible (FNS) isolates were genetically closely related. goeBURST analysis showed that DST225, DST376, DST506, and DST546 formed a distinct and unique FNS clonal complex (CC) in Wuhan. The local FNS CC belongs to the large FNS CC (CC2) in China, in which the putative founder DST225 has been reported from the environment. The three most prevalent types (DST506, DST525, and DST546) in Wuhan had high minimum inhibitory concentrations (MICs) for antifungal azoles, and the six possible nosocomial transmissions we captured were all FNS strains, most of which were from CC2. Unique FNS CCs have been found in Singapore (CC8) and India (CC17) and are close to China’s CC2 in the minimum spanning tree. There were no FNS CCs outside Asia. This study is the first to reveal a significant correlation between genetic information and fluconazole susceptibility worldwide and to trace geographical locations, which is of great value for molecular epidemiological surveillance and azole-resistance study of C. tropicalis globally.